A Study on Quadratic Game Theory formulation using Wireless Sensor Networks - Vinoba, V; Chithra, S.M; Sridevi, S (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we introduced some new concepts of the quadratic game theory and WSNs with the notions of quadratic game theory. Investigating some of their properties, we show that the formulation of quadratic game theory. For the ancient 20 years, a lot of journalists have motivated their research on wireless sensor networks. Wireless sensor networking is a broad inquiries area, and a lot of investigators have done research in the area of influence good organization to extend network lifetime